Study of some plant species as phytoremediation of heavy metals emission from oil refinery - Salih, Zhian; Muhammad , Maqsuda; Kamal, Wareen; Mazher, Runj (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
This study was carried out to investigate the phytoremediation potential of six different plant species (Melia azedaracch ,Punica granatum,Cupressus arizonica, Platanus orientalis and Platanus orientalis) in the city of Erbil mitigating heavy metal emissions of an oil refinery. The research assesses photosynthetic pigments, heavy metal concentrations (Fe, Cu, Mn, Ni, Zn, As, Pb, Co, Hg and Se) from an oil, and biochemical attributes in leaves, highlighting their responsiveness to contamination. Variations in metal levels between control and polluted sites underscore the refinery’s impact, while reduced photosynthetic pigments indicate potential ramifications for plant vigor. The intricate interplay between pollution levels and plant physiology is explored, offering crucial insights for effective environmental management strategies. Metals like Arsenic, Cadmium, Lead, and Mercury, commonly found in food, pose health risks due to human activities. The research underscores the significance of plants as indicators and reducers of pollutants, emphasizing the potential of phytoremediation in addressing environmental challenges. The findings contribute valuable information for developing sustainable approaches to combat pollution, particularly in industrial settings